Cyclam te1pa for 64Cu PET imaging. Bioconjugation to antibody, radiolabeling and preclinical application in xenografted colorectal cancer. Issue 15 (31st January 2017) - Frindel, Mathieu; Le Saëc, Patricia; Beyler, Maryline; Navarro, Anne-Sophie; Saï-Maurel, Catherine; Alliot, Cyrille; Chérel, Michel; Gestin, Jean-François; Faivre-Chauvet, Alain; Tripier, Raphaël
Abstract : te1pa conjugated to an F6 antibody was confirmed to be an interesting alternative to dota for 64 Cu in vivo PET imaging. Abstract : te1pa is a monopicolinate cyclam previously presented as a better 64 Cu chelator than dota, nota and other chelators with an improved biodistribution and in vivo resistance to transchelation. This study aimed to determine whether te1pa could improve the in vivo stability of 64 Cu chelation concerning radioimmunoconjugates in order to obtain better contrast in PET imaging. te1pa was activated on its remaining acid function to obtain a N -hydroxysulfosuccinimide ester and was then conjugated to the F6 mouse IgG1a (F6 mAb), directed against CEA (carcinoembryonic antigen), leading to the F6-te1pa immunoconjugate. F6-te1pa was compared to F6–C-dota, i.e. F6 mAb conjugated with a C -functionalized dota which is the only chelator used nowadays in preclinical trials for 64 Cu PET imaging. Immunoconjugates were radiolabeled with 64 Cu showing an equivalent conjugation rate of 1 ligand per mAb. The study of the complexation kinetics highlighted a relatively fast process and 64 Cu–F6-te1pa, exhibiting a specific activity of 69.3 ± 28.9 MBq mg −1, was proved to be inert since only 4.3% of radioactivity was transchelated from the ligand to EDTA (50 000 equiv., overnight) used as a competitor. All these results are comparable with C -functionalized dota. However, in vivo studies carried out in LS174T tumor-bearing nude mice showed a limited transchelation of superoxide dismutase (SOD) into the liver; 1.6% for 64 Cu–F6-te1pa after 24 h post-injection, compared to 4.3% for 64 Cu–F6–C-dota. The uptake of 64 Cu–F6-te1pa in tumors and radioactivity distribution in organs after 24 and 48 h was satisfactory and equivalent to various standards presented in the literature. Finally, PET-phenotypic images obtained with 64 Cu–F6-te1pa at 24 h post-injection showed an excellent contrast between tumors and the healthy tissues around, which agrees well with the results of the biodistribution. The usefulness of te1pa for PET phenotypic imaging using 64 Cu has been validated. The synthesis of a bifunctional derivative of te1pa will be the next step of this work to keep the ligand properties intact.